Automotive evalution complementraty tool for recoverability and reusability / Ho Kai Keong - Ho , Kai Keong (2018)
The automotive industry manufactured products is increasing due to the incremental size of the global population. This will definitely lead to an increasing amount of automotive waste during the end of life of vehicles. The solution lies at the designing stage where the materials are chosen and multiple designs are drawn on the drawing board before mass production of vehicles. A complementary evaluation tool is needed at the designing stage for engineers and designers to determine the recovery and reusability value of the designs made by engineers and designers of respective automotive companies. It is crucial to calculate the possibility of having to recover, recycle and reuse components and parts of vehicles to reduce the waste generated at the end of life. A fuzzy based approach is proposed to evaluate the recovery and reusability value. The factors used in the evaluation of end of life vehicle include presence of hazardous substances, accessibility index, difficulties of cleaning automotive components, type of fasteners index, material compatibility and type of tools needed for disassembly. Three case studies are conducted to verify and to prove the usefulness of the evaluation complementary tool showing the different values of recover and reusability based on the factors that affect the value of the vehicle at the end of life thus affecting the amount of waste produced. The proposed complementary tool has the potential to allow automotive companies to determine the recovery and reusability value of their designs at the onset of development to comply with certain standards.